Quality Control Analysis of Glucose and Cholesterol Testing Using Levey-Jenning’s Chart At X Hospital Yogyakarta - Rahma Nadisa, Veny; Aji Bagus Widyantara; Wahid Syamsul Hadi (CV. CENDIKIA JENIUS INDONESIA, 2025)
Clinical laboratory tests, especially measurements of blood glucose and cholesterol levels, play an important role in establishing a diagnosis and monitoring the progression of diseases such as diabetes mellitus and dyslipidemia. Inaccurate test results can lead to errors in diagnosis, which can potentially impact the provision of inappropriate therapy. Therefore, the implementation of Quality Control (QC) through the Levey-Jenning's Graph method and Westgard's rule is an effective approach to ensure the accuracy and precision of laboratory test results. To determine the results of Quality Control of blood glucose and total cholesterol examinations using Levey-Jenning's Graph in the Yogyakarta at X Yogyakarta Hospital Laboratory. Analytic descriptive method with a cross-sectional approach and with Total Sampling technique. The results show good accuracy in the parameters of the examination of temporary blood glucose and cholesterol. While precision is out of the range that has been determined. Evaluation of Levey-jenning's graph and Westgard's rule obtained 1₂ₛ dan 1₃ₛ. Conclusions on the examination of the parameters of temporary blood glucose and cholesterol have good accuracy. However, the precision on the parameters of the current blood glucose examination was not good in July and August, while the cholesterol parameter had good precision and the evaluation results were exposed to rule 1₂ₛ dan 1₃ₛ. It is recommended that the laboratory continue to improve quality management through routine calibration, consistent application of SOPs, and regular monitoring of the quality of results.